Influence of deficit irrigation on grape quality and volatile compounds in the cultivars Touriga Nacional and Touriga Franca (Vitis vinifera L.) in the Douro Demarcated Region (Portugal) - Barreales, David (2019)
The effect of deficit irrigation on grape composition and volatile compounds in Touriga Nacional and Touriga Franca grapes (Vitis vinifera L.) was investigated over one growing season in the semi-arid sub-region Douro Superior of Douro Demarcated Region (RDD). The region is characterized by a Mediterranean climate, with very dry and warm summers that cause a strong water stress in most of the vineyards. The deficit irrigation tested corresponded to 25% of the reference evapotranspiration, compared to rainfed conditions. The irrigation started at the beginning of the veraison and ended at the harvest. We evaluated the yield and vigour per vine and the qualitative parameters of grapes and musts: berry weight and diameter, Ravaz index pH, total acidity, total soluble solids (ºBrix), total polyphenol index and volatile compounds. The volatile compounds were assessed by headspace solid-phase microextraction and gas chromatography–mass spectrometry (HS-SPME-GC/MS). The results indicate that the yield per vine was significantly higher in the irrigated plants. For Touriga Nacional there was an increase of 24.5% compared to rainfed vines (from 0.77 kg vine-1 to 1.02 kg vine-1) and for Touriga Franca an increase of 35.67% (from 1.10 kg vine-1 to 1.71 kg vine-1) was observed. For total soluble solids, in both varieties, higher values were obtained in rainfed grapes. Other quality parameters of the must also showed significant differences. With respect to volatile compounds, were identified and quantified mainly C6 compounds and others lipid-derived aldehydes and alcohols, terpenoids and esters. In general, higher amounts of volatile compounds were obtained in the rainfed grapevines. The results obtained could broaden our understanding of the deficit irrigation of grapevine in sub-region Douro Superior of RDD to find a balance between yield and quality grape. Furthermore, this kind of studies very important in a climate change scenario, expected for this region in the next decades.